Combining Microarray Technology and Molecular Epidemiology to Identify Genes Associated with Invasive Group B Streptococcus - Lixin Zhang; Usha Reddi; Usha Srinivasan; Sheng Li; Stephanie M. Borchardt; Parvathy Pillai; Puja Mehta; Anne N. Styka; Joan DeBusscher; Carl F. Marrs; Betsy Foxman (Interdisciplinary Perspectives on Infectious Diseases)
Many bacterial species function as both commensals and pathogens; we used this dual nature to develop a high-throughput molecular epidemiological approach to identifying bacterial virulence genes. We applied our approach to Group B Streptococcus (GBS). Three representative commensal and one invasive GBS isolates were selected as tester strains from a population-based collection. We used microarray-based comparative genomic hybridization to identify open reading frames (ORFs) present in two sequenced invasive strains, but absent or divergent in tester strains. We screened 23 variable ORFs against 949 GBS isolates using a GBS Library on a Slide (LOS) microarray platform. Four ORFs occurred more frequently in invasive than commensal isolates, and one appeared more frequently in commensal isolates. Comparative hybridization using an oligonucleotide microarray, combined with epidemiologic screening using the LOS microarray platform, enabled rapid identification of bacterial genes potentially associated with pathogenicity.